Design factors contributing to the success of business premises at urban public plaza area - Harun, Nor Zalina; Zakariya, Khalilah; Mansor, Mazlina (American Scientific Publishers, 2017)
This research is an initial approach to formulate appropriate design policies and development management responses in planning for the continued development of the retail and recreational sectors. This research aims to identify the factors that contribute to the success of urban plaza and its business premises. It reveals how the lack of success of business premises at urban plazas is evidenced when a traditional bazaar located next to an urban square was relocated to the underground level of a shopping complex. Three main methods of collecting data are employed in this research; observation and mapping, questionnaire survey and semi structured interview. The research key findings highlighted that a high quality of design in retail development can make an important contribution to delivering quality in the built environment. It is hoped that this research could provide an insight for developers, designers and retailers the evidence-based quality principles to ensure that new retail developments play their part in realizing quality outcomes in relation to urban landscape design.